Strengthening and weakening factors for breastfeeding from the perspective of the nursing mother and her family - Lívia Perissé Baroni Wagner; Verônica de Azevedo Mazza; Silvana Regina Rossi Kissula Souza; Anna Chiesa; Maria Ribeiro Lacerda; Larissa Soares (Revista da Escola de Enfermagem da USP, 2020)
Abstract Objective: To describe the strengthening and weakening factors for breastfeeding. Method: This is a descriptive multiple case qualitative study, conducted in Curitiba, Parana, with members of 17 families with children between 6 and 12 months old, through semi-structured interview and construction of genograms, analyzed by the strategy of cross case synthesis. Results: 28 people participated in the study. Strengthening factors for breastfeeding were: the desire to breastfeed; child with facility for breastfeeding; mother with time available to the child; previous breastfeeding experience and family history of breastfeeding; the support and encouragement to breastfeed. Weakening factors were: negative expectations; the myth of weak milk; child’s disease; maternal illness; negative experiences of the mother; the absence of family history of breastfeeding; lack of a support network. Conclusion: Breastfeeding is a family and social phenomenon. Therefore, practices that go beyond the mother-baby dyad are necessary. The care process should include the social and subjective dimension, strengthening the support network of nursing mothers, in order to obtain more satisfactory professional practices that promote breastfeeding.